Faktor Utama yang Mendorong Pelanggan untuk Kembali Ke Starbucks Indonesia: Kualitas Pelayanan, Harga, Experiental Marketing - Diah Pranitasari; Rizki Kurnia; Dodi Prastuti; Pristina Hermastuti; Enung Siti Saodah (Yayasan Literasi Sains Indonesia, 2024)
This research aims to determine service quality, price and Experiential Marketing on Repurchase Intention at Starbucks Coffee Indonesia in Green Pramuka Square, East Jakarta. The research method used in this research is quantitative, with the research strategy used by researchers being an associative/causality strategy. The population in this research is all visitors to Starbucks Coffee at Green Pramuka Square, East Jakarta from January to March 2024. This research uses primary data by distributing questionnaires to 200 customers of Starbucks Coffee Store Green Pramuka Square. The sampling technique used was random sampling. The data processing method in this research uses the SPSS program. The research results conclude: 1.) service quality influences Repurchase Intention. 2.) Price influences Repurchase Intention. 3.) Experiential Marketing: Sense influences Repurchase Intention. 4) Experiental Marketing: Feeling influences Repurchase Intention 5) Experiental Marketing: Think influences Repurchase Intention 6) Experiental Marketing: Act influences Repurchase Intention 7) Experiental Marketing: Relate influences Repurchase Intention 8.) Service Quality, Price and Experiental Marketing simultaneously influences Repurchase Intention.